Substantia Nigra Hyperechogenicity Reflects the Progression of Dopaminergic Neurodegeneration in 6-OHDA Rat Model of Parkinson’s Disease - Zhang, Siyan; Tao, Kai; Wang, Jia; Duan, Yunyou; Wang, Bao; Liu, Xi (Frontiers in Cellular Neuroscience, 2020)
Parkinson’s disease (PD) is the second most common neurodegenerative disease, while there is still no effective way to stop its progress. Early detection is crucial for the prevention and treatment of Parkinson's disease. However, the current diagnosis of Parkinson's disease mainly depends on the symptoms, so it is necessary to establish a reliable imaging modality for PD diagnosis and its progression monitoring. Others’ and our previous studies demonstrated that substantia nigra hyperechogenicity (SNH) was detected by transcranial sonography (TCS) in the ventral midbrain of PD patients, and SNH is regarded as a characteristic marker of PD. The present study aimed to explore whether SNH could serve as a reliable imaging modality to monitor the progression of dopaminergic neurodegeneration of PD. The results revealed that the size of SNH was positively related with the degree of dopaminergic neuron death in PD animal models. Furthermore, we revealed that microglia activation contributed to the SNH formation in substantia nigra (SN) in PD models. Taken together, this study suggests that SNH through TCS is a promising imaging modality to monitor the progression of dopaminergic neurodegeneration of PD.